Menganalisis Penanganan Kebocoran Data Pengguna Facebook Dalam Konteks Manajemen Sekuriti - Sudirman, Muzakki; Handayani, Milda; Fauzi, Achmad; Devianti, Faysa Firli; Gunawan, Nabila Alifiyah; Puspita, Ayu Diah; Makruf, Muhammad Nafis; Musyaffa, Arif (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
The misuse of information technology for cyber crimes such as online gambling, pornography, carding, phishing, and hacking increases the risk of leaking users' personal data, as seen in the case of Facebook, due to the lack of privacy protection by technology companies. Risks and security threats from social media and sharing personal information online are also on the rise, while the lack of codified regulations for personal data protection in Indonesia poses a problem. The research aims to understand how Facebook addresses user data leaks and the obstacles faced in cyber security in Indonesia. The analysis employs qualitative techniques and literature studies, gathering data and information from online articles, journals, and books. The research findings conclude that Facebook has secured data to protect user privacy. However, with the rapid advancement of technology, increasingly complex cyber crimes pose a growing threat to data security. Awareness of cyber security among the Indonesian public remains limited